PENINGKATAN HASIL BELAJAR KIMIA MATERI LARUTAN ASAM-BASA DAN KEAKTIFAN SISWA DENGAN MODEL PEMBELAJARAN IBL BERPENDEKATAN SETS (Universitas Negeri Semarang, 2020)
This study aims to increase: 1) the outcome of chemistry learning students which Good criteria in a value of ≥ 80, 2) the activity of students through the application of IBL learning model with SETS approach on acid-base solution material. The research used 2 (two) cycles. Each cycle consists of four stages, they are planning, implementation, observation and reflection. Each cycle did in 4 until 5 meetings. The collecting data used testing, observation and documentation method. Data was analyzed descriptively by percentage. The subjects of this study were students in class XI-IPA 4 of 14 Semarang State Senior High School on the 2017/2018 Academic Year, totaling 36 students. The average value students in the first cycle was 86 with obtained value ≥ 80 was 83%. The average value students in the second cycle was 93 with obtained value ≥ 80 was 100%. The activity of students in cycle I only 64%, and increased to 92% in cycle II. Outcome learning increase from cycle I to cycle II is proofed by the average results of cycle I pre test and posttest, consecutive 75 and 86; while in cycle II the average results of posttest reach 93 with 100% Good criteria achievement. The conclusion of this class action research is the application of IBL learning model with SETS approach can increase the outcome learning of Acid-Base Solution and the activity of students in class XI IPA-4 of 14 Semarang State Senior High School significantly